2020
DOI: 10.1017/s0008423920000918
|View full text |Cite
|
Sign up to set email alerts
|

The Partisan Impact on Local Government Dissemination of COVID-19 Information: Assessing US County Government Websites

Abstract: This study explores the relationship between local government dissemination of COVID-19 information and partisanship. The unit of analysis is all official county government websites in the United States. In particular, we investigate if there is a correlation between the overall partisanship of a county and whether a county government's website 1) mentions COVID-19, and 2) provides safety instructions concerning COVID-19. We hypothesize that mass partisanship will impact the probability that a county governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…This study highlights the ability to understand how legislators use social media (eg, Twitter); what information they choose to share; and how they frame their content, which was determined through sentiment analysis [ 15 ]. These are key insights that will remain important to the public and health care systems as policy makers continue to shape the national and local responses to the pandemic [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the ability to understand how legislators use social media (eg, Twitter); what information they choose to share; and how they frame their content, which was determined through sentiment analysis [ 15 ]. These are key insights that will remain important to the public and health care systems as policy makers continue to shape the national and local responses to the pandemic [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rocco et al (2021) revealed that subnational COVID-19 data quality, including mortality, is associated with media independence. Hansen et al (2021) pointed out that in the United States, counties were more likely to release information about COVID-19 when there was a stronger opposition (Democrats) before the US presidential election. In our analysis, governments that applied censorship and spread fake news as blame avoidance behaviors may also intentionally underreport the numbers of infected and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that law enforcement agencies have the capacity for vast information dissemination but selectively decide which information to disseminate to the mass public (Aiello and Gumbhir, 2016;Kilburn and Krieger, 2014). Other supporting research on county and city websites demonstrates that governmental agencies have a fairly large capacity to disseminate information (Baker andChin, 2016, Bearfield andBowman, 2017;Bernick et al, 2014;Hansen et al, 2021;Harder and Jordan, 2013;Lowatcharin and Menifield, 2015;Yavuz and Welch, 2014). While there is variance in terms of the amount of information on these websites, overall, these websites do a fairly good job of demonstrating a commitment to information sharing.…”
Section: Research On Law Enforcement Online Presencementioning
confidence: 99%
“…At present, research on governmental agency websites is still ripe for academic investigation. At the local PIJPSM 45,2 governmental level, there are only a handful of studies that explore county or city government websites for the types and amount of information made publicly available (Armstrong, 2011;Baker and Chin, 2016;Bearfield and Bowman, 2017;;Bernick et al, 2014;Hansen et al, 2021;Harder and Jordan, 2013;Lowatcharin and Menifield, 2015). Similarly, information availability and the quality of this information on law enforcement agency websites have garnered academic interest (Aiello and Gumbhir, 2016; Barthe and Lateano, 2006;Dykehouse and Sigler, 2000;;Farmer and Copenhaver, 2021;;Jones and de Guzman, 2012;Kilburn and Krieger, 2014;Madichie and Hinson, 2014;Rosenbaum et al, 2011;Sillince and Brown, 2009;Tully and McKee, 2000;Yavuz and Welch, 2014).…”
mentioning
confidence: 99%